Inventory credit, a system to improve food security in sub-Saharan Africa - Le Cotty, Tristan; Maître d’Hôtel, Élodie; Porgo, Issoufou; Subervie, Julie; Soubeyran, Raphaël (Perspective, 2023)
Version française de l'article Inventory credit is being developed in several Sahelian countries. This device is implemented by a farmers’ organisation and a financial institution. It consists in storing a portion of harvested grain in a warehouse for several months in exchange for an individual loan. Without this loan, farmers tend to sell their grain immediately after harvesting in order to pay off their debts or to meet their needs. The consequence is that families subsequently struggle to get through the lean season – the transition period between the depletion of food stocks and the new harvest – and to invest in their agricultural production systems. An impact assessment study conducted in western Burkina Faso shows that inventory credit increases food availability in the lean season and boosts agricultural investment and production. To accelerate its development, three conditions must be met: providing access to suitable storage facilities; ensuring the quality of products stored; and building trust between financial institutions, producers’ organisations and traders. The latter condition is undermined by the expansion of armed conflicts in the Sahel.